A burned body with a shotgun head injury found on an "altar" made of banknotes: A case report from Greece and brief review of the literature. (July 2021) - Alexandri, Maria; Koukoulis, Andreas-Nikolaos; Tsellou, Maria; Papadodima, Stavroula
Highlights: Forensic investigation of burnt corpses needs careful consideration of all data. The differentiation among complex suicide or postmortem burning may be challenging. The case is presented as a suicide with a unique scene of death implying a ritual. Abstract: We describe an unusual case of a burnt body with a shotgun head injury found on a "bed" made of wooden boards on a pile of banknotes, resembling an altar. The body belonged to a 64-year-old man, of Greek nationality, with cancer who set his house (including the room in which he was found) and vehicle on fire before shooting himself, planning this way his postmortem burning. The combination of fire with the use of an "altar" and the destruction of body and possessions creates a unique death scene that implies a suicide with a ritual character.